Lichen planus – a clinical guide. (7th June 2021) - Solimani, Farzan; Forchhammer, Stephan; Schloegl, Alexandra; Ghoreschi, Kamran; Meier, Katharina
Summary: Lichen planus (LP) is a chronic lichenoid inflammatory disorder of the skin, mucosa and of the appendages. LP is classically characterized by the presence of a rich infiltration of inflammatory T cells, which migrate in the upper part of the dermis, arranged in a band‐like pattern. Different sub types of the disease have been so far described. Albeit LP is clinically well defined, the disease still represents a therapeutic enigma. Especially with regard to mucosal or scalp affecting LP types, which often present a recalcitrant and treatment unresponsive course, efficacious therapeutic options are still lacking. Thus, LP represents a disease with a high psychosocial burden. Yet, development in the deciphering of LP pathogenesis reveals possible new druggable targets, thus paving the way for future therapeutic options. In this clinical guide, we summarize the current clinical knowledge and therapeutic standards and discuss the future perspective for the management of LP.